A single 2000-meter exercise test to assess exercise adaptation in elite rowers during the preparatory phase - Kaczmarczyk, Sabina; Kasperska, Anna; Dziewiecka, Hanna; Ostapiuk-Karolczuk, Joanna; Cichoń-Woźniak, Justyna; Basta, Piotr; Skarpańska-Stejnborn, Anna (Frontiers in Physiology, 2025)
IntroductionA 2000-m exercise test on a rowing ergometer is intended to determine the training program’s effectiveness and the proper training intensity. However, anecdotal data from rowers confirm that this test involves extremely high levels of exercise, which may induce metabolic stress. Therefore, this observational study aims to analyze the effects of a 2000-m exercise test on biomarkers of inflammation, oxidative stress, and the immune system during the preparation phase in elite rowers.MethodsThe Polish Youth National Rowing Team participated in the study (N = 18). The rowers performed a 2000-m exercise test on a rowing ergometer. Before the exercise test, after one and 24 h afterwards, venous blood was taken to determine biomarkers. Pro-oxidant-antioxidant balance parameters (total antioxidant capacity, thiobarbituric acid reactive substances), pro- and anti-inflammatory cytokine levels (IL-2, IL-10, TNF-α, IL-6), and MYO were determined. This is part of a study that has been registered on clinicaltrials.gov under the identifier NCT06133751.ResultsA statistically significant increase in IL-6 concentrations was observed 24 h after exercise. IL-10 concentrations statistically decreased significantly immediately after and 24 h post exercise. MYO levels statistically decreased significantly immediately after and 24 h post exercise. WBC statistically increased significantly immediately after exercise and then returned to baseline values.ConclusionThe results of this study confirm that the 2000-m exercise test causes short-term inflammation, which is related to the physiological recovery process. In addition, chronic inflammation and immune system disturbances were not observed, which means that the athletes showed adaptation to very intense exercise.